Evaluating the Anti-Ulolithiatic Potential of A Methyl Extract from the whole Hygrophila Salicifolia plant using the in Vitro method of Urolithiasis Induction by Ethylene Glycol (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Utilising an in vivo approach to induce urolithiasis with ethylene glycol, the research examines the anti-urolithiatic potential of a methanolic extract derived from the whole Hygrophila salicifolia plant. Over the course of 28 days, five groups of male Wistar albino rats were randomly assigned to different treatment groups. The first group was used as a control, the second group got a lithiatic agent, the third group had Cystone, and the fourth and fifth groups got two doses of the methanolic extract. From the urine samples, many parameters were analysed, including the amounts of calcium, creatinine, phosphate, magnesium, and oxalate. The development of calcium oxalate monohydrate (COM) crystals was significantly inhibited by the methanolic extract in comparison to the control and other extracts.  A significance threshold of P